Genome-Wide Identification of the TIFY Family in Longan and Their Potential Functional Analysis in Anthocyanin Synthesis - Haowei Qing; Ziang Wu; Xiao Mo; Jinjv Wei; Yuyu Shi; Huiqin Guo; Jiongzhi Xu; Feng Ding; Shuwei Zhang (Biology)
TIFY is one of the plant-specific transcription factors, which is extensively involved in regulating plant development, stress response, and biosynthesis of secondary metabolites. In this study, we identified 19 DlTIFY genes from the longan genome data. All of them contained the conserved TIFY domain, and these 19 DlTIFYs were distributed on 9 out of the 15 chromosomes of longan. A phylogenetic tree was constructed based on the TIFY protein sequences from Arabidopsis, rice, orange, and grape. They were clustered into six groups, with the TIFYs from longan showing the closest homology to those from orange. Duplication events were present between DlTIFY1 and DlTIFY5, DlTIFY4 and DlTIFY6, and DlTIFY16 and DlTIFY17. There are several light-responsive elements, Abscisic Acid (ABA)-, Gibberellic Aci (GA)-, and Methyl Jasmonate (MeJA)-responsive elements, in the promoter regions of longan TIFY genes. Additionally, the flavonoid biosynthetic gene regulation elements were presented in the promoter of DlTIFY7, DlTIFY10, and DlTIFY11, suggesting their involvement in flavonoid synthesis regulation of longan. We also found that the expression of DlTIFY7 in the stem and pericarp was significantly higher than that in other tissues. Interestingly, the outer edge of the corolla exhibited a green hue with a faint reddish tint across the corolla in transgenic tobacco plants overexpressing DlTIFY7. Subcellular localization experiments confirmed that DlTIFY7 is expressed in the nucleus. These findings suggest that DlTIFY7 may serve as a novel candidate transcription factor negatively regulating anthocyanin synthesis in longan. This study provides valuable insights into the functional characterization of longan DlTIFY genes and lays a foundation for future research on their roles in regulating plant development and secondary metabolism.